Changing nature of capitalism and the evolution of geographical space - Sachinder Singh (National Geographical Journal of India, 2025)
The article discusses the history and development of capitalism, as well as its expressions in geographical space. Since the Great Depression (1929-1939), capitalism has transformed from the stage of organized capitalism to disorganized capitalism. The changing role of the state as a sovereign territorial entity in the functioning of organized capitalism and disorganized capitalism has created different kinds of economic landscapes. It has also been observed that since the early 1970s, the state has not only promoted but also created more avenues for the growth of private capital in geographical space. In the present context, space is considered to be neither fixed nor neutral to social actions. Rather, it is treated as a social construct.